Influences of Advertisement on Buying Behaviour - A.A. Gde Satia Utama; Rajesh Kumar Nair; Wan En Cheng; Daisy Mui Hung Kee; ZeXian Chen; Min Ru Cheng; ZiHang Cheng; Shruti Talesara (AIBPM Publisher, 2021)
In this era of advanced technology, sellers are provided with different methods, platforms, and designs to prepare their advertisements. This study examines the ways advertisement influences consumer buying behavior in Malaysia and India. A total of 100 responses were collected from surveys to 51 Malaysian respondents and 49 Indian respondents from universities’ groups, personal friends, and families. The findings indicate that advertising is highly persuasive. Also, we identify that social media ad achieve the most affecting advertising channels. We have also identified the difference of view about the influences of advertisement before and after the pandemic.